Implementasi Take Away Sebagai Konsep Penjualan pada Outlet Makanan Cepat Saji - Dhiya’u Shidiqy (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
This research was conducted to describe the concept of selling with a takeaway and the motivation behind consumers in choosing to buy by taking away at Hakui Kopi, Tulungagung Station. The approach in this study uses a qualitative descriptive approach with analysis techniques using an interactive analysis model. The results showed that the number of purchase orders by taking away at Hakui Kopi Station was more dominant than purchase orders with online and dine-in applications, while the product units sold were dominated by purchases with online applications. There is also the practicality of orders and the practicality of consumption which are the dominant factors behind and become the motives of consumers in making take away purchases. The distance and access to shops are also dominant motives compared to other motives, namely psychological, lifestyle, socioeconomic, and advertising effects.